The Determinants of Waqf Preference Toward Money-Cash Waqf - Jauhar Faradis (Global Review of Islamic Economics and Business, 2015)
This research is based on the lackness of societie’s understanding toward cash Waqf and its big chance. The purpose of this research is to understand the factors causing Waqf preference toward the product of money-cash Waqf. The method of this research is factors analysis, and is applied in the Province of Yogyakarta include: Yogyakarta City, Sleman, Kulonprogo, Bantul and Gunung Kidul Regency. The results of this research are the determinants of muslim sociatie’s preference toward Money-Cash Waqf are: wakif’s attitude factor, complain factor, productive action factor, equity factor, product characteristic factor, and religiosity factor as well as generosity factor.